Multiple conceptualizations of nature are key to inclusivity and legitimacy in global environmental governance. Issue 104 (February 2020) - Coscieme, Luca; da Silva Hyldmo, Håkon; Fernández-Llamazares, Álvaro; Palomo, Ignacio; Mwampamba, Tuyeni H.; Selomane, Odirilwe; Sitas, Nadia; Jaureguiberry, Pedro; Takahashi, Yasuo; Lim, Michelle; Barral, Maria P.; Farinaci, Juliana S.; et al.
Highlights: We examined diverse conceptualizations of nature in more than 60 languages. Inclusive and non-inclusive natures imply humans as part of, or separate from, nature. Deifying natures depict nature within a spiritual dimension. Diverse conceptualizations of nature influence environmental policy and future scenarios. Acknowledging this diversity is key to representative environmental governance. Abstract: Despite increasing scientific understanding of the global environmental crisis, we struggle to adopt the policies science suggests would be effective. One of the reasons for that is the lack of inclusive engagement and dialogue among a wide range of different actors. Furthermore, there is a lack of consideration of differences between languages, worldviews and cultures. In this paper, we propose that engagement across the science-policy interface can be strengthened by being mindful of the breadth and depth of the diverse human-nature relations found around the globe. By examining diverse conceptualizations of "nature" in more than 60 languages, we identify three clusters: inclusive conceptualizations where humans are viewed as an integral component of nature; non-inclusive conceptualizations where humans are separate from nature; and deifying conceptualizations where nature is understood and experienced within a spiritual dimension. Considering and respecting this rich repertoire of ways of describing, thinking about and relating to nature can help us communicate in ways that resonate across cultures and worldviews. This repertoire also provides a resource we can draw on when defining policies and sustainability scenarios for the future, offering opportunities for finding solutions to global environmental challenges.